2012
DOI: 10.1016/j.postharvbio.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrostatic atomization on ascorbate metabolism in postharvest broccoli

Abstract: In the present study, the effects of electrostatic atomization on ascorbate (AsA) metabolism were studied and the possible molecular mechanisms were discussed in broccoli (Brassica oleracea L. var. italica). With the treatment of electrostatic atomization, the yellowing process was delayed, and the ethylene production and respiration rate were significantly suppressed in broccoli after harvest. In the meanwhile, the AsA content declined rapidly to a lower level in the control after harvest, and the reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
6
13
1
Order By: Relevance
“…Variations in the level of ascorbic acid during the circadian rhythm has been observed (Chang, Yang, & Riskowski, ) and it has been hypothesized that these variations could be due to light–dark cycles and photosynthetic activity (Ivanov, ). In any case, the ascorbic content decreased in the same way in all samples during storage as senescence progressed, as it is described in other researches (Ma et al, , ).…”
Section: Resultssupporting
confidence: 86%
“…Variations in the level of ascorbic acid during the circadian rhythm has been observed (Chang, Yang, & Riskowski, ) and it has been hypothesized that these variations could be due to light–dark cycles and photosynthetic activity (Ivanov, ). In any case, the ascorbic content decreased in the same way in all samples during storage as senescence progressed, as it is described in other researches (Ma et al, , ).…”
Section: Resultssupporting
confidence: 86%
“…AsA levels can be elevated in plants by increasing the gene expression of MDAR and DHAR [8] and [53]. In broccoli, the up-regulation of BO-MDAR1, BO-MDAR2, and BO-DHAR contributed to maintaining a high AsA content after harvest with an electrostatic atomization treatment [11]. In the present study, the results showed that the gene As shown in Fig.…”
Section: Effects Of Blue Led Light On the Expression Of Genes Relatedsupporting
confidence: 56%
“…As there is a mutation in the AsA biosynthetic enzyme L-galactono-1,4-lactone dehydrogenase (GLDH), humans cannot synthesize the AsA in the body and must obtain it through the daily diet. In recent years, to meet health requirements and the growing demand of consumers for highly nutritional foods, AsA metabolism in plants has been extensively investigated, and several efforts have been made to enhance AsA levels in fruits and vegetables [8], [9], [10], [11], [12] and [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1-MCP) and electrostatic atomization were effective in delaying yellowing and decay, alleviating certain ethylene-induced postharvest physiological disorders, and suppressing the reduction of AsA in broccoli after harvest (Ma et al, 2009(Ma et al, , 2010(Ma et al, , 2012a.…”
Section: Introductionmentioning
confidence: 99%